Dynamic energy assessment to analyze different refurbishment strategies of existing dwellings placed in Madrid. (1st June 2018) - Soutullo, S.; Giancola, E.; Heras, M.R.
Abstract: The application of the European directives related to the energy consumption of existing buildings leads to the integration of efficient techniques into the refurbishment actions. This procedure allows reaching high energy savings and reducing pollutant emissions. The identification of the energy consumption profile of the building stocks is a necessary step to evaluate the impact of retrofit measures. With this aim, the energy performance of representative dwellings has been analyzed to develop a citizen-oriented platform. This representativeness has been chosen through one parametric matrix that characterizes the residential building stock of Madrid. Different refurbishment strategies have been highlighted to assess the energy savings in comparison with the initial situation. Two building cases and three boundary conditions have been selected to develop six TRNSYS models. The energy impact produced by the implementation of selected refurbishment strategies has been evaluated through a sensitivity analysis. Batteries of simulations have been executed coupling the TRNSYS models with GenOpt. The most influential strategies are the typology of façades, insulation at the roof, variable set point temperatures, better glazing and exterior summer shading over the windows. Building performances to minimize the annual thermal needs and one economic study have been developed. Graphical abstract: Image Highlights: Energy assessment of existing dwellings stock placed in Madrid. A decision support tool for the evaluation of the building energy performance. Dynamic simulations coupling between TRNSYS and GenOpt were done. Sensitivity analysis to highlight the most influential strategy implemented. Energy and economic evaluation of the best refurbishment actions.